2007
DOI: 10.1002/jcb.21119
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 signaling in a hepatoma cell line is skewed towards apoptosis

Abstract: Toll-like receptors (TLRs) recognize pathogen-associated molecular patterns (PAMPS) leading to the activation of the innate immune response and subsequently to the shaping of the adaptive immune response. Of the known human TLRs, TLR3, 7, 8, and 9 were shown to recognize nucleic acid ligands. TLR3 signaling is induced by double-stranded (ds)RNA, a molecular signature of viruses, and is mediated by the TRIF (TIR domain-containing adaptor-inducing IFNbeta) adaptor molecule. Thus, TLR3 plays an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 53 publications
6
56
0
3
Order By: Relevance
“…[24][25][26][27][28] or activation of RNA-dependent protein kinase (PKR; refs. [29][30][31][32][33].…”
Section: Il4ra Mediates a Prosurvival Signaling In Mdscsmentioning
confidence: 99%
“…[24][25][26][27][28] or activation of RNA-dependent protein kinase (PKR; refs. [29][30][31][32][33].…”
Section: Il4ra Mediates a Prosurvival Signaling In Mdscsmentioning
confidence: 99%
“…It is an interesting paradox that TLRs are expressed in invasive cancerous cells. TLR3 is expressed in breast cancer (10), melanoma (11), prostate cancer (12), cervical cancer (13), colon cancer (13), hepatocellular carcinoma (14) and head and neck cancer (15), while TLR4 is expressed in lung cancer (17). In HNSCCs, studies of TLR expression have been reported by only two investigators (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…These unique pathways also induce T-cell activation and differentiation, which result in immune responses against tumor cells. On the other hand, an investigator has recently reported that stimulation of TLR3 could directly cause tumor cell apoptosis (10)(11)(12)(13)(14). In breast cancer (10), melanoma (11), prostate cancer (12), cervical cancer (13), colon cancer (13) and hepatocellular carcinoma (14), TLR3 directly induced cell apoptosis with poly I:C. However, only one study was reported in HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trial did not however differentiate the role that Poly A:U and radiotherapy had as single therapies (Laplanche, 2000). Several studies have reported that caspase 3 is up-regulated by TLR3 agonist activity which would suggest a role for caspase 3 in cancer cell apoptosis induced by TLR3 agonists (Salaun, 2006;Khvalevsky, 2007). A recent study by Conforti et al demonstrated the synergistic effects between vaccines, chemotherapy and poly A:U (Conforti, 2010).…”
Section: Toll-like Receptor-3mentioning
confidence: 97%